Pengaruh Keyakinan Religius, Peran Sertifikasi Halal, Paparan Informasi, Dan Alasan Kesehatan Terhadap Kesadaran Masyarakat Pada Produk Makanan Halal - Pramintasari, Talisa Rahma; Fatmawati, Indah (Universitas Muhammadiyah Yogyakarta, 2017)
This study aims to analyze the Influence Of Religious Belief, Role Of Halal Certification, Information Exposure And Health Reason Of People’s Awareness On Halal Foods. The setting in this study measuring the level of awareness of halal food products in Yogyakarta. Objects of research in the area is Kotagede, while the subject is the individual Muslim in the area is. Kotagede chosen because it is the region's civilization is the Islamic Mataram Kingdom and Muhammadiyah also rapid growth, so that the majority of the population was Muslim. In this study, sample of 117 respondens were selected using technique non-probability sampling and purposive sampling manifold. Alanysis tool used in this study is the multiple linear regression. Based on the analysis that have been made results are the religious belief have a significant impact on the awareness of halal, role of halal certification has a significant influence on the awareness of halal.